Strengthening Teacher's Pedagogical Competence and Students’ Learning Motivation During The Covid-19 Pandemic - Aunurrahman Aunurrahman; Chairil Effendi; M Asrori; Tomo Djudin (Universitas Tanjungpura, 2021)
The Community Service Program aims to convey and discuss and reflect in-depth on strengthening teacher pedagogical competence and student learning motivation in online learning during the Covid-19 Pandemic. This activity was carried out at SMKN 2 Singkawang by involving teachers from SMKN 2 and SMKN 5 Singkawang. The aspects discussed specifically include; (1) strategies for strengthening teacher pedagogical competencies, (2) very essential pedagogical dimensions that are mastered and applied by teachers, (3) appropriate and applicable learning guidance patterns for students, (4) communication and speech patterns that can motivate and appropriate in supporting the implementation of online learning during the Covid-19 pandemic. The activities were carried out in the form of seminars involving 110 teachers. The results of the PKM get a common perception about the importance of strengthening students' competence and learning motivation during the covid-19 period. Meanwhile, based on the reflection of teacher learning, what needs to be developed regarding strategies for strengthening teacher competencies and student learning motivation is that the strengthening strategies must be directed at strengthening digitalization competencies, literacy, and communication competencies to strengthen students' knowledge, attitudes, and skills.